The combined effects of the provision of feed and healthcare on nutrient utilization and growth performance of sheep during the early or late dry season - Konlan, Solomon Pigangsoa; Ayantunde, Augustine A.; Addah, W.; Dei, H.K. (Springer, 2017)
An on-farm study was conducted to determine the combined effects of the provision of feed and healthcare on nutrient use and growth performance of sheep during the early or late dry season. A total of 36 smallholder sheep farmers with a flock size of ≤7 was randomly selected within each of the three administrative regions in Northern Ghana. The sheep grazed on a heterogeneous natural pasture and offered crop residues as basal diet (control) or were additionally provided with a concentrate feed plus orthodox healthcare to control diseases and pests (CH) in a completely randomized block design. The provision of orthodox healthcare included scheduled control of endo- and ecto-parasites and administration of broad-spectrum antibiotics. Data was analyzed for the fixed effects of CH, season, or CH × season using the mixed model procedure of Genstats®. The CH regimen had no effect (P = 0.098) on intake of natural pasture but pasture intake increased (P = 0.012) during the late dry season. Sheep on the CH regime had higher DM (P = 0.026) and N (P = 0.068) digestibility and improved ADG (P = 0.001) and feed conversion efficiency (P = 0.020) than those on the control. We hypothesize that improvements in growth performance of sheep on the CH regimen could be related to availability of nutrients for growth that will otherwise have been used for repair of damaged tissues caused by gastrointestinal parasites and ticks. Sheep on the CH regimen also had a higher concentration of fecal N during the late dry season when CP concentration was relatively higher than that in the early dry season (63.2 vs 60.9 g/day DM) when CP concentration of pasture was lower.